2023
DOI: 10.1101/2023.03.14.532478
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Principles of human pre-60Sbiogenesis

Abstract: During early stages of human large ribosomal subunit (60S) biogenesis, an ensemble of assembly factors establishes and fine-tunes the essential RNA functional centers of pre-60Sparticles by an unknown mechanism. Here, we report a series of cryo-electron microscopy structures of human nucleolar and nuclear pre-60Sassembly intermediates at resolutions of 2.5-3.2 angstroms. These structures show how protein interaction hubs tether assembly factor complexes to nucleolar particles and how GTPases and ATPases couple… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…2a). Thus Dbp10, like the DEAD-box ATPases Has1 and Spb4, remains bound to the pre-60S post-catalytically, a state recently captured in cryo-EM reconstructions of human and C. thermophilum pre-60S intermediates 20,21 . These studies also show that another RBF exchange, the removal of the Nsa1/Mak16/Rpf1/Rrs1 module by Rix7, appears to occur independently from Dbp10 function.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…2a). Thus Dbp10, like the DEAD-box ATPases Has1 and Spb4, remains bound to the pre-60S post-catalytically, a state recently captured in cryo-EM reconstructions of human and C. thermophilum pre-60S intermediates 20,21 . These studies also show that another RBF exchange, the removal of the Nsa1/Mak16/Rpf1/Rrs1 module by Rix7, appears to occur independently from Dbp10 function.…”
Section: Resultsmentioning
confidence: 87%
“…In turn, Rrp14 release removes a steric block to allow the organization of the C-terminal anchoring domain of Spb1. In addition to its C-terminal methyltransferase domain, Spb1 contains multiple modules that interact with 15 other pre-60S components, including the Noc2/Noc3 heterodimer, acting as a critical hub to assemble rRNA domain III 20,21,31,35,36 . These sequential events therefore directly link PTC maturation and domain III organization, revealing how a non-equilibrium, ATP-dependent step is directly connected to subsequent structural changes in the pre-60S.…”
Section: Discussionmentioning
confidence: 99%
“…3C and D). Recently, structural efforts have demonstrated that LSU maturation proceeds through at least eight nucleolar intermediates, States A-H 41 . Mapping the LSU clusters onto these structures revealed that LSU1 was primarily enriched for factors involved in earlier stages of LSU assembly (States A-F), while LSU2 contained factors that associate with later intermediate species (States G and H), most notably all components of the 5S RNP, a core component of the central protuberance (CP) that is thought to bridge LSU functional centers 42,43 and mediate intersubunit communication with the SSU 44 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This trend suggests that the buildup of strongly interacting, early ribosomal precursors with high valency limits NPM1 mobility, while accumulation of low valency, late pre-ribosome intermediates allow NPM1 to exchange more readily. Indeed, the transition from State F to G/H, which differentiates LSU1 and LSU2, involves the stabilization of several 28S rRNA domains 41 , which could result in a significant decrease in rRNA valency and contribute to the increase in dynamics we see for LSU2 genes. These observations are consistent with a model where the strength of interactions with NPM1 may determine not only the propensity to phase separate into the nucleolar condensate, but also macromolecular dynamics.…”
Section: Changes In Npm1 Dynamics Are Associated With Shifts In Ribos...mentioning
confidence: 92%
“…Previous research on ribosome biogenesis primarily focused on factors facilitaLng the proper assembly of the ribosome [21][22][23] . By contrast, invesLgaLons into quality control mechanisms targeLng abnormal pre-ribosomes remain relaLvely unexplored.…”
Section: Introduc8onmentioning
confidence: 99%